Development and validation of a drug clinical trial participation feelings questionnaire for cancer patients - Guo, Chaowei; Xing, Shujun; Zhao, Guo; Wu, Dawei; Li, Ning; Wang, Shuhang; Yu, Ling (Frontiers in Pharmacology, 2024)
Objective The study was designed to develop and validate a new drug clinical trial participation feelings questionnaire (DCTPFQ) for cancer patients. Methods Data collection and analysis involved a combination of qualitative and quantitative methods. There were two phases to this study. Phase Ⅰ involved developing a questionnaire to establish a list of items to be included in the pool: A theoretical framework was constructed based on the transitions theory and the Roper–Logan–Tierney theory. After incorporating a theoretical framework, interviewing participants, and reviewing the literature, 44 items were generated. After a Delphi consultation and a pilot test, 36 items proceeded to item analysis and exploratory factor analysis (EFA), and a four-factor structure with 21 items was formed. Confirmatory factor analysis (CFA), test–retest reliability, criteria-related validity, and internal consistency tests were conducted in phase II to examine the psychometric properties. Results There were 21 items on the DCTPFQ, ranging from 1 (fully disagree) through 5 (fully agree). As a result of EFA and CFA, the four factors of DCTPFQ could be verified, including cognitive engagement, subjective experience, medical resources, and relatives and friends’ support. Test–retest reliability of the DCTPFQ was 0.840, and Cronbach’s alpha was 0.934. DCTPFQ is significantly correlated with the Fear of Progression Questionnaire—short form (r = 0.731, p < 0.05) and the Mishel’s Uncertainty in Illness Scale (r = 0.714, p < 0.05). Conclusion The DCTPFQ is a useful tool for measuring the drug clinical trial participation feelings among cancer patients.